Synergistic Effect of Pectinolytic and Proteolytic Enzymatic Clarification on Cantalopue Juice - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Cantaloupe is consumed worldwide thanks to its sweetness, juicy taste, pleasing flavor, and nutritional value. It’s highly perishable under ambient condition if fresh consumption cannot move quickly. It’s urgent to process this therapeutic fruit in industrial scale. In fact, it can be processed into different products including functional juice. Clarity in fruit juices is desirable to make it useful in international standard. Objective of this study focused on the effectiveness of various processing variables affecting to cantaloupe juice turbidity and clarity. In our research, a mixture of pectinase and protease in different concentration (0.03%:0.07%, 0.04%: 0.06%, 0.05%:0.05%, 0.06%:0.04%, 0.07%:0.03%), holding temperature (26, 28, 30, 32, 34oC), holding time (45, 60, 75, 90, 105 min), pH (4.3, 4.5, 4.7, 4.9, 5.1), agitation (250, 500, 750, 1000, 1250 rpm) were examined. Carotenoid (µg/g), flavonoid (g/L), turbidity (NTU) and viscosity (cP) were key indicators to determine the optimal treatment. Our results showed cantaloupe fruit juice would have the best carotenoid, flavonoid, clarity as well as viscosity  by treatment of pectinase: protease ratio concentration 0.06%: 0.04%, temperature 20oC in 75 min at pH 4.7 with agitation 1000 rpm. Synergistic effect of the combined usage of pectinase and protease enzymes was clearly demonstrated. From this finding, the added value of cantaloupe juice would be improved in storage as well as commercial distribution without any worry about haze cloud.Keywords: Cantaloupe, Juice, Pectinase, Protease, Carotenoid, Flavonoid, Turbidity, Viscosity.